Potensi Penambahan Bahan Organik Terhadap Sporulasi dan Infektivitas Beauveria Bassiana Pada Larva Oryctes Rhinoceros - Sipayung, Yeni Octavia Kita; Nion, Yanetri Asi; Adrianson Agus Djaya (Jurnal Penelitian UPR, 2023)
This study aims to determine the potential for adding organic matter in this case the effect of differences in media composition on the growth and sporulation of B. bassiana and in the infectivity of Beauveria bassiana against the larvae of rhino beetle pest (Oryctes rhinoceros). The experiment was carried out using a Completely Randomized Design (CRD) with 2 series, namely: a). Different types of growing media (M) on B. bassiana consisted of 6 treatments P1: PDA (Potato Dextrose Agar) media; P2: SDYA Media (Sabouraud Dextrose Yeast Agar) + mineral water; P3: SDYA media + coconut water, P4: SDYA media + coconut water + cricket flour 10%; P5: SDYA media + coconut water + grasshopper flour 10% ; P6: SDYA media + coconut water + 10% chicken eggshell flour where each treatment was repeated 5 times b). The application of B. bassiana on O. rhinoceros larvae consisted of 7 treatments, namely P0, P1, P2, P3, P4, P5 and P6, each treatment repeated 4 times. The fastest growth in diameter of B. bassiana was found in SDYA media + eggshell flour but treatment SDYA + coconut water + cricket flour (P4) had the highest percentage of fungus germination and had the highest density of B. bassiana spores, also had highest mortality percentage to suppress O. rhinoceros. The latest finding that has not been found by other researchers before is the discovery of modified SDYA + coconut water media with the addition of chicken egg shell flour to accelerate the growth of B. bassiana and SDYA + coconut water + cricket flour media to promote spore germinations of B. bassiana and increases the ability to suppress of O. rhinoceros.